User satisfaction analysis of e-filing system in reporting annual tax returns for individual taxpayers - Nurlanda, Balqis Yessa; Saebani, Akhmad (WIM Solusi Prima, 2025)
This study aims to determine the effect of system quality, service quality, and ease of use on user satisfaction of the e-Filing tax system for individual taxpayers. The existence of complaints related to technical aspects and understanding of use indicates the importance of evaluating user satisfaction. Therefore, this study was conducted to analyze the extent to which users are satisfied with the e-Filing system in reporting Annual Tax Returns, so that it can be the basis for improving tax services in the future. The research approach used is a quantitative method with primary data, and sampling using the snowball sampling technique. The research sample collected and processed was 127 samples with individual taxpayer respondents. The research data was processed using the Structural Equation Model with the help of SmartPLS 4 statistical software with a significance level for accepting the research hypothesis of 5%. The results of testing the research hypothesis indicate that the variables of system quality and ease of use have a significant positive effect on user satisfaction of the e-Filing tax system for individual taxpayers. However, the variable of service quality does not affect user satisfaction of the e-Filing tax system for individual taxpayers.